IMPLEMENTATION OF RISK MANAGEMENT: FINANCING-BASED HAJJ FUND INVESTMENT IN THE HAJJ FINANCIAL MANAGEMENT AGENCY (BPKH) - Harsanto, Molbi Febrio; Muslim, Habibie; Suratminingsih, Suratminingsih; Arifin, Samsul; Was'an, Guruh Herman (Dirasa Islamiyya: Journal of Islamic Studies, 2024)
The Hajj Financial Management Agency (BPKH) is a state institution that manages Hajj finances. The long waiting period for hajj departures and the great desire of the community to perform the hajj pilgrimage make the hajj funds managed by BPKH continue to grow significantly every year. BPKH has a share of 10% of the total managed funds that can be invested in the form of sharia financing. Strong risk management is needed to be able to invest in the form of financing. This study uses a qualitative method with interview and observation techniques to explore the opinions of competent parties. The results of this study show that the role of Risk Management is very vital in the investment activities carried out by BPKH, especially in the Financing Segment. The conclusion of this study is that risk management can help BPKH improve financial performance, and BPKH in general is still not optimally prepared to further participate in the contest with banks in the field of financing. The recommendation from this study is that BPKH should further improve the infrastructure and quality of human resources that carry out risk management analysis because this can provide security for Hajj funds.